2015
DOI: 10.1159/000439238
|View full text |Cite
|
Sign up to set email alerts
|

New Options of Apheresis in Renal Diseases: How and When?

Abstract: The 100-year anniversary of the first experimental apheresis performed by John Abel on uremic dogs in 1914 provides the opportunity for discussion on the current state of classic apheresis as well as technological progress and clinical experiences with its new options presented in the world literature in the last 15 years, such as the following: double filtration, plasma adsorption and immunoadsorption, leuko- and cytapheresis and low-density lipoprotein apheresis. In our review, we highlight the potential lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Removal of these macromolecules has proven succesful in achieving a total remission, usually as a support to immunosuppressants. 65 Plasmapheresis in the course of MM was first employed in 1952 in patients with a hyperviscosity syndrome. 66 Actually, plasmapheresis was the only extracorporeal technique available to remove circulating FLC until 2005.…”
Section: Renal Apheretic Techniquesmentioning
confidence: 99%
“…Removal of these macromolecules has proven succesful in achieving a total remission, usually as a support to immunosuppressants. 65 Plasmapheresis in the course of MM was first employed in 1952 in patients with a hyperviscosity syndrome. 66 Actually, plasmapheresis was the only extracorporeal technique available to remove circulating FLC until 2005.…”
Section: Renal Apheretic Techniquesmentioning
confidence: 99%
“…Therapeutic apheresis (TA) is an extracorporeal blood purification method employed in treating renal diseases caused by the accumulation of immune complexes, allo-or autoantibodies, and cryo-or immunoglobulins in the patient's plasma. Removal of those substances by way of apheresis promises either a total remission (apheresis as a primary treatment) or improved results of an immunosuppressive treatment (apheresis as a supporting treatment, [108]). The first attempts at a therapeutic application of plasmapheresis were conducted in 1952 on patients with a hyperviscosity syndrome in the course of MM [109]; plasmapheresis was the only extracorporeal technique capable of removing circulating FLCs until 2005.…”
Section: Treatment Of Aki By Renal Apheresis: High-cutoff Membrane Hemodialysismentioning
confidence: 99%
“…However, by using 2 HCO-1100 dialyzers in series and, therefore, doubling the membrane surface area, there was a greater increase in FLC clearance and FLC reduction ratios [114,115]. Subsequently, it was shown that patients who received effective chemotherapy regimens and adjunctive HCO-HD had a much better renal recovery rate than historical controls [101,108,116]. The most relevant studies on FLC removal by using HCO filters were published in 2007 and 2008 by the same group [103,105].…”
Section: Treatment Of Aki By Renal Apheresis: High-cutoff Membrane Hemodialysismentioning
confidence: 99%
“…24 Hence, an assessment of the efficiency of existing and emerging apheresis techniques in relation to ultra-selective blood component extraction is required, while considering the cost-effectiveness in more mature technologies. 12 So far, limited studies described key performance characteristics of the existing apheresis technologies [25][26][27][28][29] and few comprehensively benchmarked current practices to emerging and alternative technologies, such as microfluidic-based or sorbentbased apheresis. 30 The impact of materials used or the operating parameters on the removal efficiency are also seldomly discussed.…”
Section: Introductionmentioning
confidence: 99%